Asceticism Practices on Mount Kumbang in the 15th-16th Century: Praktik Asketisme di Gunung Kumbang Abad XV-XVI M - Sunjana, Dani; Saringendyanti, Etty; Nugrahanto, Widyo (BRIN, 2024)
Asceticism practices constitute an integral part of religious and cultural life in Tatar Sunda society during the classical period, which remains understudied. This research serves as a preliminary study on asceticism practices in Mount Kumbang, Brebes, during the 15th-16th centuries, highlighting the ideological backgrounds and ascetic practices occurring in the region. The research was conducted through historical archaeology approach. The findings indicate that asceticism practices in Mount Kumbang during the 15th-16th centuries are documented in written and archaeological sources. The existence of these practices is rooted in religious ideologies associated with achieving spiritual power and the highest level of knowledge, accomplished through various forms of psychophysical restraint such as meditation (samadhi), fasting, and specific rituals.